User Satisfaction towards Implementation of Emerging Technologies in Library, University College of Science, MLSU Udaipur (LIS TODAY, 2026)
The present study examines the user satisfaction level of RFID technology and facilities provided in the Library, University College of Science (UCoS), Mohanlal Sukhadia University, Udaipur, Rajasthan. The main objective of the study was to know the level of satisfaction with RFID-enabled library services, to examine the utilization of Self-Check In/Check-Out by software and Check-In/ Check-Out by staff, and to assess the satisfaction of users with RFID technology.A self-designed questionnaire was used to collect data from 367 students out of 4,472 registered users. A total of 336 respondents were chosen from the University College of Science, MLSU Udaipur. The findings of the study have depicted that most of the respondents were fully satisfied with RFID technology and library services that are provided to physically impaired users. In Self-Check-In/Out, the majority of users were using Self-Check-In/Out by software.
Keywords: RFID technology, satisfaction level, library resources, Self-Check-In/ Check-Out, Mohanlal Sukhadia University, and faculty members.